Numerical analysis of downwash airflow distribution from multi-rotor UAV in soybean-maize strip intercropping canopy - Xinghua Liu; Lei Yang; Yang Li; Zhi Li; Fan Jiang; Yanping Tian; Xiang-Dong Li (Biosystems Engineering, 2026)

Effective strategy for simultaneous removal of Congo red and Cr(VI) by ferroan brucite - Shifeng Zhao; Xin Fan; Fengzhu Lv; Yanping Zhao; Yuli Cui (Journal of Water Process Engineering, 2026)

Effects of different morphologies of CeOₓ on the unsaturated Mn/Co defects of MnOₓ/CoOₓ catalysts for highly active photothermocatalysis of acetone and NO - Siqi Jiang; Sihan Li; Yinming Fan; Yanping Zhang; Shengpeng Mo; Lei Liao; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2026)

Long-term PFOA and cadmium Co-contamination alters soil carbon, nitrogen, and phosphorus cycling: Insights from metagenomics and metabolomics - Yanping Cai; Beihai Zhou; Shuming Liu; Chuyu Shang; Baoguo Yang; Yunqing Liu; Shengguang Zhang; Ruixue Fan; Waseem Hassan; Rongfang Yuan; Huilun Chen (Environmental Research, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Fabrication of RuCo bimetallic catalyst enabling efficient hydrogen generation via ammonia borane hydrolysis - Xianyun Liu; Lu Zhao; Han Wu; Linyan Bian; Yanping Fan; Baozhong Liu (Fuel, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Non-invasive Computational Techniques for Diagnosing Myocardial Ischemia: Challenges and Future of FFRCT/iFRCT - Bao Li; Jincheng Liu; Yang Yang; Hao Sun; Chi Zhu; Leo Hwa Liang; Zijie Wang; Luyao Fan; Suqin Huang; Xueke Li; Guangfei Li; Liyuan Zhang; et al. (Annals of Biomedical Engineering, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Hour-level humification of papermaking waste residue to produce honeycomb-like controlled-release fertilizer - Dongqing Cai; Shuang Wang; Linying Wang; Zerong Song; Yanping Zhu; Ziyu You; Jinjing Xu; Yan Wang; Wanji Zhu; Rongjun Zhang; Pan Zhao; Xiaofeng Lu; et al. (Journal of Cleaner Production, 2026)

Performance and mechanism of Co-MOF@BiVO4 sol-gel/graphite felt cathode for antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Xi Li; Naif Abdullah Al-Dhabi; Zuofang Yao; Songyu Fan; Chenchen Xing; Yujia Liu; Hongxiang Zhu; Wangwang Tang; Yanping Hou (Journal of Environmental Chemical Engineering, 2025)

Enhanced dehydrogenation kinetics and cyclic stability of NaAlH4 through nitrogen coupling with Ti3C2 MXene - Zhenluo Yuan; Ruyi Guo; Xiuxiu Zhang; Jiabao Cai; Haiwen Li; Qiuming Peng; Shumin Han; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2025)

Biochar-Amended Composting Transforms Chicken Manure Waste Into a Resource: Enhancing Extra-Rhizosphere Soil Fertility and Shaping Microbial Communities - Longjun Chen; Haiping Fan; Lulong Zhong; Yuncai Wang; Cheng Chen; Xin Chen; Yanping Chen; Jiaolin Zhang; Yu Lin (Journal of Soil Science and Plant Nutrition, 2025)
This study elucidates the synergistic regulatory mechanisms of biochar-amended chicken manure and mushroom residue compost (BCM) on soil microbial communities and nutrient cycling in the extra-rhizosphere, while evaluating its potential for sustainable agricultural waste recycling. Methods: We conducted a 50-day composting trial using five biochar application rates (0–7%). Assessed parameters included compost maturity (C/N ratio), nutrient content (NO 3 − -N, available phosphorus [AP], soil organic matter [SOM]), phosphatase and catalase activities, microbial community composition, and metabolic pathways. We performed Redundancy analysis (RDA) to correlate SOM/AP dynamics with microbial diversity and functional pathways. Results: At 5–7% biochar, compost maturity improved significantly, with C/N ratios of 15.6–18.2 and 2.2-4.0-fold increases in NO 3 − -N (1.41 mg/g), AP (50.09 mg/kg), and SOM (166.11 g/kg). Enzymatic activities (phosphatase: 9.81 mg/g·24 h; catalase: 83.08 µmol/g·24 h) correlated strongly with SOM/AP (R 2 = 0.71–0.82). Biochar enriched Proteobacteria (34.1%) and Actinobacteriota (15.2%), suppressed Halophiles ( Halomonas reduced by 52%), and enhanced carbon metabolism and oxidative phosphorylation pathways. RDA identified SOM/AP as a key driver of microbial diversity (R 2 = 0.91). The 5% biochar dose optimized nutrient retention (37–59% increases in AP, Available potassium [AK], NO 3 − -N) while maintaining microbial diversity, outperforming higher doses. Conclusions: This study demonstrates biochar’s dual role in reshaping extra-rhizosphere microbial ecology and nutrient dynamics, offering a precision agriculture strategy for sustainable waste recycling and circular economy practices. The 5% biochar dosage proved optimal, enhancing nutrient cycling and microbial activity while mitigating halophilic microbial suppression. Graphical Abstract

Ru/S-modified hollow ZIF-67 for efficient sulfapyridine degradation via enhanced PMS-AOPs and inhibited of cobalt leaching - Zhuoqun Deng; Zhiyi Fan; Changchun Si; Jia Zhu; Ziyi Yang; Dexun Zou; Yanping Liu (Chemical Engineering Journal, 2025)

Insights into stress response pathways and potential triterpene accumulation mechanisms induced by friction damage in kiwifruit - Fan Yang; Yuchun Wang; Fangzhi Wu; Sike Wang; Yuduan Ding; Yue Chen; Qinggang Zhu; Yanping Ma (Postharvest Biology and Technology, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Bone marrow mesenchymal stem cells promote the recovery of stroke in rats with type 2 diabetes mellitus by inhibiting the activation of TLR4/NF-κB signaling pathway - Fan Peng; Yanping Long; Taolin Zheng; Minghui Leng; Hui Deng (Molecular and Cellular Biochemistry, 2025)

Functional integrated in gel polymer electrolytes: A handy approach for achieving superior wide temperature range operation sodium metal batteries - Yubin Liao; Fangkun Li; Yadong Zhou; Xijun Xu; Hangyu Zhang; Weizhen Fan; Yanxue Wu; Jingwei Zhao; Jun Liu; Yanping Huo (Chemical Engineering Journal, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

Adjusting Co ratios to control the unsaturated Mn defects in nanostick-assembled CoOx@MnOx double layered sphere catalysts for highly active photothermocatalysis of acetone/ethyl acetate and NO without ammonia - Yinming Fan; Weihan Wu; Yanping Zhang; Yinian Zhu; Shengpeng Mo; Lei Liao; Mingming Fu; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Postharvest fragrance dynamics of different scented cut lilies: Insights from HS–SPME–GC–MS and electronic nose - Yiwei Zhou; Yiwei Chen; Jinfeng Dong; Qin Wang; Fulong Yan; Jianjun Tan; Yechun Xu; Genfa Zhu; Yanping Fan; Yuanjun Ye (Postharvest Biology and Technology, 2025)

Neurotoxicity study of cenobamate-induced zebrafish early developmental stages - Jiahao Liu; Liya Fang; Chao Gong; Jiawei Li; Yuanyuan Liu; Pei Zeng; Yanping Fan; Yao Liu; Jin Guo; Luchuan Wang; Yue Li (Toxicology and Applied Pharmacology, 2025)

VIF-Net: Interface completion in full waveform inversion using fusion networks - Zixuan Deng; Qiong Xu; Fan Min; Yanping Xiang (Computers & Geosciences, 2025)

An interannual dipole mode of midsummer persistent extreme high-temperature days between South China and Southwest China: effects of Indo-Pacific sea surface temperature - Yanping Gao; Ke Fan; Zhiqing Xu (Climate Dynamics, 2025)

Dynamic aromatics: Evaluating fragrance quality shifts and implementation of real-time rapid detection in Hedychium cut flowers during senescence - Yiwei Zhou; Qin Wang; Xue Wei; Ting Gao; Farhat Abbas; Fulong Yan; Jingjuan He; Yunyi Yu; Rangcai Yu; Yanping Fan (Postharvest Biology and Technology, 2024)

Recombinant Marek’s disease virus type 1 provides full protection against H9N2 influenza A virus in chickens - Yuntong Chen; Qingqing Yu; Wenrui Fan; Xianying Zeng; Zibo Zhang; Guobin Tian; Changjun Liu; Hongmei Bao; Longbo Wu; Yanping Zhang; Yongzhen Liu; Suyan Wang; et al. (Veterinary Microbiology, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Numerical simulation on staggered grids of three-dimensional brinkman-forchheimer flow and heat transfer in porous media - Wei Liu; Yingxue Song; Yanping Chen; Gexian Fan; Pengshan Wang; Kai Li (Computational Geosciences, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

High recoverable energy storage density and efficiency achieved in doped NaNbO3 ceramics via composition design strategy for pulsed power capacitor - Renkai Zhao; Kaiyuan Wang; Wenhua Li; Yujia Yuan; Xingui Tang; Jia Hu; HuaXiang Fan; Kaijie Chen; Wanglai Song; Yanping Jiang; Xiaobing Guo (Chemical Engineering Journal, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Potential modulation strategy on bismuth vanadate-based semiconductor to enhance antibiotic degradation in heterogeneous electro-Fenton system - Jinghui Pan; Zimu Zhang; Zuofang Yao; Songyu Fan; Tingting Zhu; Chenchen Xing; Yujia Liu; Jianhua Chen; Hongxiang Zhu; Yanping Hou; Shuangfei Wang (Chemical Engineering Journal, 2024)

Identification and functional analysis of floral terpene synthase genes in Curcuma alismatifolia - Zihan Cao; Lan Wang; Di Huang; Guilan Wu; Xinyue Li; Yuechong Yue; Yunyi Yu; Rangcai Yu; Yanping Fan (Planta, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

V2O5·3H2O/N-doped graphite felt cathode efficiently produced H2O2 and ·OH in the electro-Fenton system for enhanced antibiotics degradation - Songyu Fan; Yanping Hou; Jiaxiang Liang; Tingting Zhu; Shiming Zhang; Ting Liang; Jinghui Pan; Yuxiang Shen; Zebin Yu; Hongxiang Zhu; Shuangfei Wang (Journal of Environmental Chemical Engineering, 2024)

Structures and ion transport mechanisms of plant high-affinity potassium transporters - Jiangqin Wang; Yanping Luo; Fan Ye; Zhong Jie Ding; Shao Jian Zheng; Shuai Qiao; Yong Wang; Jiangtao Guo; Wei Yang; Nannan Su (Molecular Plant, 2024)

Online LC-ESI-MS/MS comparative analysis of N/O-glycopatterns in human colostrum from different ethnic groups in Northwest China - Xiaoqin Wang; Jing Liu; Shukai Wang; Yutao Xie; Yipei Liu; Jiangbo Fan; Yanping Li; Yu Lu; Linjuan Huang; Zhongfu Wang (Carbohydrate Polymers, 2024)

Niacin alleviates extracellular matrix deposition in ethanol + CCl4-induced liver fibrosis through the HSP90/JAK1/STAT3 axis - Yanping Fan; Meilan Xue; Tianhu Shan; Yixian Bai; Huaqi Zhang; Man Liu; Peng Wang; Xi Liang; Hui Liang (Food Bioscience, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Understanding quality differences between kiwifruit varieties during softening - Fan Yang; Renkai Zhao; Jiangtao Suo; Yuduan Ding; Jiawei Tan; Qinggang Zhu; Yanping Ma (Food Chemistry, 2024)

Tungsten and oxygen dual vacancies regulation of the S-scheme ZnSe/ZnWO4 heterojunction with local polarization electric field for efficient CO2 photocatalytic reduction - Ting Liang; Zebin Yu; Yuejing Bin; Shiming Zhang; Jingwen Wei; Yujia Liu; Tingting Zhu; Songyu Fan; Yuxiang Shen; Shuangfei Wang; Yanping Hou (Chemical Engineering Journal, 2024)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

The built-in electric field and spin-pinning effect in BiVO4/Fe0.4Co0.6Se2/Co(Fe)OxHy for enhanced photoelectrochemical water oxidation - Ben Fan; Ling Ding; Zebin Yu; Ronghua Jiang; Yanping Hou; Shuang Li; Jianhua Chen (Chemical Engineering Journal, 2023)

Nitrogen doping excited Ru and Ti3C2−xNx support for hydrogen generation from ammonia borane - Licheng Liang; Linyan Bian; Yanping Fan; Shuyan Guan; Xianyun Liu; Qunying Sun; Baozhong Liu (Fuel, 2023)

Characterization of a newly identified RNA segment derived from the genome of Sclerotinia sclerotiorum reovirus 1 - Jichun Jia; Fan Mu; Yanping Fu; Jiasen Cheng; Yang Lin; Daohong Jiang; Jiatao Xie (Archives of Virology, 2022)

Characterization of a novel botoulivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Fan Mu; Jichun Jia; Yunxiang Xue; Daohong Jiang; Yanping Fu; Jiasen Cheng; Yang Lin; Jiatao Xie (Archives of Virology, 2021)

Genome-wide analysis of ARF transcription factors reveals HcARF5 expression profile associated with the biosynthesis of β-ocimene synthase in Hedychium coronarium - Farhat Abbas; Yanguo Ke; Yiwei Zhou; Yunyi Yu; Muhammad Waseem; Umair Ashraf; Xinyue Li; Rangcai Yu; Yanping Fan (Plant Cell Reports, 2021)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

A Hedychium coronarium short chain alcohol dehydrogenase is a player in allo-ocimene biosynthesis - Hua Chen; Yuechong Yue; Rangcai Yu; Yanping Fan (Plant Molecular Biology, 2019)

Functional characterization and expression analysis of two terpene synthases involved in floral scent formation in Lilium ‘Siberia’ - Farhat Abbas; Yanguo Ke; Rangcai Yu; Yanping Fan (Planta, 2019)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

The BET bromodomain inhibitor i-BET151 impairs ovarian cancer metastasis and improves antitumor immunity - Ai Liu; Dianxia Fan; Yanping Wang (Cell and Tissue Research, 2018)

Volatile terpenoids: multiple functions, biosynthesis, modulation and manipulation by genetic engineering - Farhat Abbas; Yanguo Ke; Rangcai Yu; Yuechong Yue; Sikandar Amanullah; Muhammad Muzammil Jahangir; Yanping Fan (Planta, 2017)

Extracellular ATP is involved in the initiation of pollen germination and tube growth in Picea meyeri - Junhui Zhou; Chengyu Fan; Kai Liu; Yanping Jing (Trees, 2015)

Characterization of two monoterpene synthases involved in floral scent formation in Hedychium coronarium - Yuechong Yue; Rangcai Yu; Yanping Fan (Planta, 2014)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Estrogen deficiency inhibits the odonto/osteogenic differentiation of dental pulp stem cells via activation of the NF-κB pathway - Yanping Wang; Ming Yan; Yan Yu; Jintao Wu; Jinhua Yu; Zhipeng Fan (Cell and Tissue Research, 2013)

Molecular Cloning and Expression Analysis of a Terpene Synthase Gene, HcTPS2, in Hedychium coronarium - Ruihong Li; Yanping Fan (Plant Molecular Biology Reporter, 2011)